A case of autoimmune myositis after treatment with alemtuzumab for multiple sclerosis. Issue 4 (December 2018) - Aouad, Patrick; Yiannikas, Con; Fernando, Suran L; Parratt, John
Alemtuzumab is a high-efficacy disease-modifying therapy for the treatment of relapsing forms of multiple sclerosis and is associated with secondary autoimmune adverse events. We report a novel case of secondary autoimmune myositis that occurred seven months after the initial treatment cycle and achieved full recovery with oral corticosteroids. This particular form of myositis appears to be unique, and is likely to be a distinct entity from the other four types of immune-mediated myositis.